2014 International Symposium on Technology Management and Emerging Technologies 2014
DOI: 10.1109/istmet.2014.6936497
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of canny and sobel operator for logo edge detection

Abstract: This study is to compare how Canny and Sobel Operators can be used as edge detection technique for various logo images. The main process involved Sobel and Canny edge detection techniques using captured logo images and logo images from internet. The images manipulated by median filtering to remove noise and Otsu's method is used to determine threshold value. The result shows that both operators have their own advantages and disadvantages to be used as edge detection aid for logo images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…We calculated the activation edge direction for each activation edge based on MATLAB's image processing algorithm for calculating directional gradient with the Sobel operator option 13 . Compared to other image processing algorithms, the Sobel operator is simple (an advantage for developing real‐time software) and can detect both edges and orientations of shapes 14 . It can however be sensitive to noise.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the activation edge direction for each activation edge based on MATLAB's image processing algorithm for calculating directional gradient with the Sobel operator option 13 . Compared to other image processing algorithms, the Sobel operator is simple (an advantage for developing real‐time software) and can detect both edges and orientations of shapes 14 . It can however be sensitive to noise.…”
Section: Methodsmentioning
confidence: 99%
“…13 Compared to other image processing algorithms, the Sobel operator is simple (an advantage for developing real-time software) and can detect both edges and orientations of shapes. 14 It can however be sensitive to noise. The activation edge direction is the mean of the gradients calculated by the Sobel algorithm.…”
Section: Activation Edge Direction and Wavefront Directionmentioning
confidence: 99%
“…The Canny operator is a multi-level edge detection algorithm based on Grayscale. Kutty et al 26 used Canny operator and Sobel operator to detect logo edges respectively, and compared the detection effects of the two operators, the results of which showed that both methods can be used as auxiliary methods for logo detection. The Sobel operator is a common edge detection operator based on first-order derivatives.…”
Section: Related Workmentioning
confidence: 99%
“…It has diverse applications, such as object detection, image segmentation, and 3D reconstruction. We use the Sobel operator (Kutty et al, 2014) to extract significant edges from two original underwater images and their enhanced versions. As depicted in Figure 15B, our method produces clearer and more complete edge structures for prominent targets in the enhanced underwater images, indicating that our method performs well in underwater image edge extraction.…”
Section: Edge Extractionmentioning
confidence: 99%